2007
DOI: 10.1177/0963662506065054
|View full text |Cite
|
Sign up to set email alerts
|

Mass media framing of biotechnology news

Abstract: Low density lipoprotein (LDL) particle size is inversely associated with plasma triglyceride concentration in cross-sectional analyses. In the present study, changes in the LDL particle size of 227 participants of the Framingham Offspring Study were analyzed longitudinally by nondenaturing gradient gel electropho-resis at two examinations that were separated by 3-4 years. All subjects had triglyceride concentrations <400 mg/dl at both exams. Using laser scanning densitometry to assess mean LDL particle size, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 36 publications
7
104
2
3
Order By: Relevance
“…As previous studies have shown, media representations have consistently overemphasized benefits, while overlooking risks and the experimental nature of these technologies [Caulfield, 2004;Bubela and Caulfield, 2004]. Furthermore, longitudinal studies have shown a general positive bias in media framing of human biotechnologies vis-à-vis agricultural biotechnologies [Marks et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have shown, media representations have consistently overemphasized benefits, while overlooking risks and the experimental nature of these technologies [Caulfield, 2004;Bubela and Caulfield, 2004]. Furthermore, longitudinal studies have shown a general positive bias in media framing of human biotechnologies vis-à-vis agricultural biotechnologies [Marks et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the Hungarian press coverage to the results of some media analyses of the coverage in Western countries we can see that the issue was of lower salience in the Hungarian press and the treatment was particularly negative (Cook et al, 2006;Marks et al, 2007). A comparison of the results to my earlier findings on the media representation of stem cell research and treatment (Vicsek, 2011;Vicsek & Gergely, 2011) also shows that similarly to what was found in many other countries (Bauer, 2005a), in Hungary too a difference could be seen in the applied media frames for red and green biotechnology, with negative frames utilized more often in the case of green biotechnology.…”
Section: Mass Media Framing Of Gm Cropsmentioning
confidence: 91%
“…Previous studies (which did not include Hungary in their sample) showed that whereas in the early nineties in numerous societies the media applied similar frames with respect to medical and agricultural applications of biotechnology, over time in many countries the media increasingly differentiated between these applications, and applied divergent frames. The media representation of agri-food biotechnology became more negative, with a concern frame employed more often in connection with the issue (Bauer, 2005a;Bauer, Kohring, Allansdottir, & Gutteling, 2001;Marks, Kalaitzandonakes, Wilkins, & Zakharova, 2007).…”
Section: The Mass Media Arenamentioning
confidence: 99%
“…8.9 These findings are in accord with the results of an analysis of European media coverage of biotechnology. 10,11 However, these earlier studies failed to present the whole picture of Japanese media coverage on GM because the sample sizes were small compared to the total number of published articles on GM. In addition, the time frame covered by these reports was strictly limited and they focused on the analysis of 2 or 3 topics, e.g.…”
Section: Introductionmentioning
confidence: 99%